Mapping of health care facilities, dental visits and oral health problems in Indonesia to prevent COVID-19 transmission - Ayu Asri Lestari; Melissa Adiatman; Risqa Rina Darwita (Dental Journal, 2022)
Background: One of the goals of Indonesia’s participation in sustainable development goals is to improve its health state. Efforts to achieve health improvement are increasing the availability of health care facilities so people can easily access and get treatment for dental and oral health. As we know, the first case of COVID-19 in Indonesia was found in March 2020 and all cases were spread over 34 provinces. During this pandemic situation, health care facilities and some dental treatments generating aerosols are one of the environments that can potentially transmit COVID-19 to the community. Dentists have the riskiest job because they must be less than two meters from patients. Purpose: This study aimed to evaluate the distribution of health care facilities, dental visits and oral health problems to prevent increased exposure to COVID-19 by using a geographic information system to explore the distribution of regional data. Methods: This study is a secondary data analysis and used data from Indonesia Basic Health Research 2018 and Health Facility Research 2019. Data of health care facilities, dental visits and oral health problems were tabulated using MS Excel version 16.45. Spatial mapping was done using Quantum Geographic Information System Desktop version 3.18.3 based on open-source software. Results: Java Island has the highest distribution of health care facilities and receives treatment from the dentist. COVID-19 reached a peak in June–July 2021, and Java Island became the region with the highest incidence rate. Conclusion: The distribution of health care facilities and dental visits was in line with the spread of the COVID-19 virus in 34 provinces. Almost all treatments of oral health problems need a highspeed rotary instrument, which can be a source of transmission of this virus.